41. A CASE OF SALIVARY GLAND ADENOMA WITH DUCTAL DIFFERENTIATION WITH MORPHOLOGICAL RESEMBLANCE TO NORMAL STRIATED DUCTS. (February 2015) - Ardakani, N. Mesbah; Parry, J.; Sterrett, G.
Abstract : Back ground: WHO classification of salivary gland adenomas includes a morphological spectrum based on cellular and stromal components. Pure ductal adenoma is not a valid entity in the current WHO classification. Clinical data: A 73 year old woman underwent a parotidectomy with clinical suspicion of pleomorphic adenoma. On follow up at 32 months, there was no evidence of recurrence or metastasis. Pathological findings: Grossly a relatively circumscribed 22 mm tumour was identified. Histologically it was composed of ductal structures lined by columnar cells with eosinophilic cytoplasm and no cytological or architectural features of malignancy. The ducts showed a great resemblance to normal striated ducts. On immunohistochemistry the lesional cells exhibited an epithelial phenotype (positive for AE1/3, CK7, and CEA) and immunostains for myoepithelial markers failed to demonstrate a myoepithelial component. Electron microscopy attributed an epithelial nature to the tumour with ultrastructural features suggestive of intermediate ducts. Discussion: This case demonstrated features of a benign neoplasm, although difficult to subtype. Entities including pleomorphic adenoma, oncocytoma, basal cell and canalicular adenoma were considered in the differential diagnosis. On immunomorphological grounds, there was a great resemblance to striated ducts. A series (6 cases) of striated duct adenomas has been previously reported in the literature. The current tumour had an essential histological resemblance to those cases, although EM failed to prove a definite striated duct origin. Conclusion: We report a case of salivary gland neoplasm with ductal differentiation intermediate between striated and intercalated ducts. We believe pure ductal salivary gland adenomas are uncommon but do exist and should be considered in the differential diagnosis if appropriate morphological features are identified.